(untitled) (Research, Society and Development, 2021)
The cranial vena cava syndrome (CVCS) is the physical manifestation of the obstruction of the blood flow of this vessel, causing a reduction in the flow of venous return towards the right atrium. Its clinical symptoms are unspecific, and range from dyspnea, cough, cyanosis, dysphagia, edema of the face, tachycardia, neck veins dilation, cachexia, muffled heart sounds, pulmonary silence, and engorgement of the jugular veins and thorax. This paper reports the case of CVCS in a male six-year-old Golden Retriever dog, as a result of a tumor in the base of the heart, in the right atrium. During his first visit to the emergency clinic, the animal presented pain to abdominal palpation, congestion of the mucous membranes, facial edema, skull muscle loss, cardiac hypophonesis, and crackling pulmonary auscultation. Having as support the exams that were performed in the patient, as hemogram, biochemical, echocardiogram, chest X-ray and pericardial effusion cytological analysis, it was defined the therapeutic conduct so that the clinical picture was softened. The animal died 18 days after the beginning of its treatment. The necropsy allowed us to conclude the diagnosis, and the tumor was classified as hemangiosarcoma, a malignant and aggressive neoplasm that originates from vascular endothelium cells, and it is considered responsible for a high mortality rate in dogs, especially in the German Shepherd and Golden Retriever breeds. When it is located in the heart, it is common for hemangiosarcoma to grow in the right atrium.